Preparation method for producing ultra-pure oxygen-free copper rod through up-drawing continuous casting method

By controlling multiple process parameters in the upper-induction continuous casting method, the oxygen content of the oxygen-free copper rod is reduced, and its resistivity, elongation and torsion resistance are improved, the problem of high oxygen content of the oxygen-free copper rod in the prior art is solved, and the large-scale stable production of ultra-high-purity oxygen-free copper rods is achieved.

CN119857833APending Publication Date: 2025-04-22BAIYIN NONFERROUS NORTHWEST COPPERPROCESSING CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510056220.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The oxygen-free copper rods produced by the current continuous casting method have high oxygen content and cannot meet international requirements.

Method used

By controlling the mass of the cathode copper sheet, the copper liquid temperature, the solidification and supercooling of the copper rod, the casting rod speed, the crystallizer conditions, and the reduction of charcoal and graphite scales, the upper-induction continuous casting method is used to traction of the oxygen-free copper rod in a three-body furnace composed of a melting furnace, a transition chamber and an insulation furnace.

Benefits of technology

The oxygen content of oxygen-free copper rods is reduced to below 3ppm, and the resistivity, elongation and torsion resistance meet the national standard requirements, which improves the application added value of oxygen-free copper rods and is suitable for high-end fields of electrical vacuum devices such as electronic components, high-frequency transmitters and vacuum switches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005241514470000041
    Figure BDA0005241514470000041
Patent Text Reader

Abstract

The invention discloses a preparation method for producing an ultra-pure oxygen-free copper rod through an up-drawing continuous casting method, and belongs to the technical field of metal material machining. Comprising the following steps: selecting a cathode copper sheet as a raw material, performing oxygen-free copper rod traction in a three-body furnace consisting of a melting furnace, a transition bin and a holding furnace by adopting an up-drawing continuous casting method, adding the dried electrolytic copper sheet and charcoal into the melting furnace, and adjusting the temperature of a melt in the melting furnace; the molten copper liquid automatically flows into a transition bin to be subjected to standing and impurity removal, and charcoal and graphite flakes are laid on the surface of the copper liquid; a graphite crystallizer is inserted into molten copper, a guide rod is connected, a guide rod is prepared, the inlet and outlet water temperature of the crystallizer is adjusted, and the traction speed and pitch of a cast rod are set. According to the method, the oxygen content of the produced ultra-pure oxygen-free copper rod can be reduced to 3 ppm or below by controlling the quality of the cathode copper sheet of the copper rod, the temperature of the copper liquid, the solidification supercooling degree of the copper rod, the rod casting speed, the conditions of the crystallizer and combined control over charcoal and graphite flake reduction, and the application additional value of the oxygen-free copper rod is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material processing, in particular to a preparation method for producing an ultra-high purity oxygen-free copper rod by an upward continuous casting method. Background Art

[0002] Oxygen-free copper rods can be divided into T1 (≤400ppm), TU1 (≤10ppm), T2 (≤450ppm), TU2 (≤20ppm), T3 (≤500ppm), etc. according to the oxygen content. Due to its good electrical and thermal conductivity, it is widely used in conductive bars, transformer belts, electromagnetic wires, vacuum devices and other products. Since vacuum devices need to be sealed in hydrogen during the manufacturing process, strict requirements are placed on the oxygen content of copper rods. With the continuous improvement of industrial technology, the performance indicators of copper rods produced by the existing continuous casting and rolling method and the up-drawing method are far from meeting international requirements. The oxygen content of oxygen-free copper rods produced by the continuous casting and rolling process is about 250-450ppm, which is far from meeting international requirements. The oxygen content of oxygen-free copper rods produced by the domestic up-drawing method is about 10ppm, which is still a gap from the requirements of ultra-high purity oxygen-free copper rods. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method of ultra-high purity oxygen-free copper rod produced by upward continuous casting, which solves the problem of high oxygen content in oxygen-free copper rod produced by the existing upward continuous casting method.

[0004] The technical solution adopted by the present invention is as follows:

[0005] A method for preparing an ultra-high purity oxygen-free copper rod by an upward continuous casting method comprises the following steps:

[0006] S1: cathode copper sheet is selected as raw material;

[0007] S2: Add the dried electrolytic copper sheet and charcoal into the melting furnace, adjust the melt temperature of the cathode copper in the melting furnace to 1150±5℃, and maintain the copper liquid level at 500mm~580mm;

[0008] S3: The molten copper liquid flows to the transition bin for static removal of impurities. 80mm to 200mm thick baked charcoal and graphite flakes are laid on the surface of the copper liquid to further reduce and purify the copper liquid. The ash and slag generated in the furnace bin are cleaned in time, and new charcoal is added. During the process, ensure that the copper liquid cannot be exposed to the air;

[0009] S4: insert the graphite crystallizer into the copper liquid, connect the guide rod and start preparing the guide rod, adjust the inlet water temperature of the crystallizer to 20℃~30℃, the outlet water temperature to 25℃~45℃, the inlet and outlet temperature difference to 5℃~15℃, the water pressure to 0.2MPa~0.3MPa, set the traction speed of the casting rod to 1m / min~1.5m / min, and the pitch to 3mm~4mm;

[0010] S5: After the rod is led out, the guide rod is disassembled in sections and enters the take-up system through the guide wheel frame, the intermediate bracket and the limit device, and the produced copper rod is randomly inspected.

[0011] In step S1, the surface of the selected cathode copper sheet is smooth and flat without obvious surface defects, and the content of impurity elements is controlled to be: As≤10ppm, Fe≤30ppm, Sb≤10ppm, Bi≤10ppm, Pb≤10ppm.

[0012] In step S4, ensure that the graphite crystallizer is inserted into the copper liquid to a depth of 150 mm to 170 mm.

[0013] Preferably, in step S2, the liquid level of the copper liquid is maintained at 530 mm to 550 mm.

[0014] Preferably, in step S3, the thickness of the charcoal and graphite flakes laid on the surface of the copper liquid is 100 mm to 150 mm.

[0015] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0016] 1. The present invention solves the problem of high oxygen content in oxygen-free copper rods produced by the existing upward continuous casting method. By controlling the quality of copper rod cathode copper sheets, copper liquid temperature, copper rod solidification undercooling, rod casting speed, crystallizer conditions, and charcoal and graphite flake reduction combined control, the oxygen content of the produced ultra-high purity oxygen-free copper rod can be reduced to below 3ppm. Compared with TU1 oxygen-free copper rod, the oxygen content is significantly reduced, and the resistivity, elongation and torsion resistance all meet the national standard requirements, which greatly improves the added value of the application of oxygen-free copper rods, and can be applied to high-end fields of electric vacuum devices such as electronic components, high-frequency transmitting tubes, and vacuum switches.

[0017] 2. The performance of the ultra-high purity oxygen-free copper rod produced by the present invention meets the requirements of GB / T 3952-2016, and its resistivity is 0.01699Ω·mm2 / m; elongation at break is 43%; tensile strength is 393MPa; and torsion resistance is 25r forward and 102r reverse.

[0018] 3. The φ8-φ12.5 mm oxygen-free copper rod produced by the present invention has a stable process and can achieve large-scale stable production. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the specific data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0020] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] This embodiment provides a method for producing an ultra-high purity oxygen-free copper rod by an upward continuous casting method, comprising the following steps:

[0023] Cathode copper sheets from a certain company were selected as raw materials. The surface of the selected cathode copper sheets was smooth and flat, without obvious surface defects. Control included but was not limited to the content of impurity elements: As≤10ppm, Fe≤30ppm, Sb≤10ppm, Bi≤10ppm, Pb≤10ppm. The upward continuous casting method was used to pull φ8mm oxygen-free copper rods in a three-body furnace consisting of a melting furnace, a transition bin and a holding furnace.

[0024] Specifically, the dried electrolytic copper sheet and charcoal are added to the industrial frequency induction melting furnace, the melt temperature of the cathode copper in the melting furnace is adjusted to 1145°C, and the copper liquid level is maintained at 500mm; the molten copper liquid flows to the transition bin for static removal of impurities, and 150mm thick baked charcoal and graphite flakes are laid on the surface of the copper liquid to further reduce and purify the copper liquid, and the ash generated in the furnace bin is cleaned in time, and new charcoal is added, and during the process, it is ensured that the copper liquid cannot be exposed to the air;

[0025] Insert the graphite crystallizer into the copper liquid, connect the guide rod and start preparing the guide rod, adjust the inlet water temperature of the crystallizer to 20℃, the outlet water temperature to 25℃, the water pressure to 0.2MPa~0.3MPa, set the traction speed of the casting rod to 1mm / min, and the pitch to 3mm; after the rod is led out, remove the guide rod in sections, and enter the take-up system through the guide wheel frame, the intermediate bracket and the limit device, and conduct random inspection on the produced copper rods. The inspection results are shown in Table 1 below.

[0026] Example 2

[0027] Cathode copper sheets from a certain company were selected as raw materials. The surface of the selected cathode copper sheets was smooth and flat, without obvious surface defects. Control included but was not limited to the content of impurity elements: As≤10ppm, Fe≤30ppm, Sb≤10ppm, Bi≤10ppm, Pb≤10ppm. The upward continuous casting method was used to pull φ8mm oxygen-free copper rods in a three-body furnace consisting of a melting furnace, a transition bin and a holding furnace.

[0028] Add the dried electrolytic copper sheet and charcoal to the melting furnace, adjust the melting furnace temperature to 1150℃, and keep the copper liquid level at 550mm. The melted copper liquid flows to the transition bin for static removal of impurities. 200mm of charcoal and graphite flakes are laid on the surface of the copper liquid to further reduce and purify the copper liquid, and the ash produced in the furnace bin is cleaned in time, and new charcoal is added. During the process, ensure that the copper liquid cannot be exposed to the air. Insert the graphite crystallizer into the copper liquid, connect the lead rod to prepare the lead rod, the inlet water temperature is 25℃, the outlet water temperature is 35℃, the traction speed of the copper rod is 1.3mm / min, and the pitch is 3mm. After the copper rod is led out, the lead rod is disassembled in sections, and enters the take-up system through the guide wheel frame, the intermediate bracket and the limit device. The produced copper rods are randomly inspected, and the test results are shown in Table 1 below.

[0029] Example 3

[0030] The cathode copper sheet of a certain company was selected as the raw material, and the upper continuous casting method was used to process the φ8mm oxygen-free copper rod in a three-body furnace consisting of a melting furnace, a transition furnace and a holding furnace. The dried electrolytic copper sheet and charcoal were added to the melting furnace, and the temperature of the copper liquid in the melting furnace was adjusted to 1155℃, and the copper liquid level was maintained at 580mm. The molten copper liquid flows to the transition bin for static removal of impurities, and 150mm of charcoal and graphite flakes are laid on the surface of the copper liquid to further reduce and purify the copper liquid. The graphite crystallizer is inserted into the copper liquid, and the lead rod is connected to prepare the lead rod. The inlet water temperature is 30℃, the outlet water temperature is 40℃, the copper rod traction speed is 1.5mm / min, and the pitch is 3mm. After the copper rod is led out, the lead rod is disassembled in sections, and enters the take-up system through the guide wheel frame, the intermediate bracket and the limit device. The produced copper rods are randomly inspected, and the test results are shown in Table 1 below.

[0031] Table 1 Performance test data of the embodiment

[0032]

[0033] In summary, the oxygen content of the ultra-high purity oxygen-free copper rod produced by the present invention can be reduced to below 3ppm. The performance of the ultra-high purity oxygen-free copper rod produced by the present invention meets the requirements of GB / T 3952-2016, and its resistivity is 0.01699Ω·mm2 / m; elongation at break: 43%; tensile strength: 393MPa; anti-torsion: after 25r of forward rotation, it breaks after 102r of reverse rotation. The φ8~φ12.5mm oxygen-free copper rod produced by the present invention has a stable process and can achieve large-scale stable production.

[0034] The invention adopts an upward continuous casting method to mass-produce φ8-φ12.5 mm oxygen-free copper rods. By controlling the quality of raw materials, the temperature of molten copper, the solidification undercooling degree of the copper rods, the casting speed, the crystallizer conditions, the charcoal and graphite flakes and other process parameters, the oxygen content of the oxygen-free copper rods is reduced while the resistivity, elongation and tensile strength and other properties thereof meet the national standard requirements.

[0035] The melt temperature of the cathode copper after melting is too high, which leads to an increase in the air intake of the copper rod melt, making the solidification structure of the copper rod coarse and the pores larger; when the copper liquid temperature is too low, the metal fluidity is poor, which is not conducive to shrinkage compensation, and defects such as loose crystallization, broken rods, slag inclusions, and cold shuts are prone to occur.

[0036] The solidification supercooling degree of the copper rod is related to the water temperature and water pressure at the inlet and outlet of the crystallizer. The smaller the temperature gradient from the middle to the edge of the casting rod, the finer the grains after metal crystallization, the higher the strength of the casting rod, and the better the plasticity.

[0037] The process parameters such as the casting rod speed, crystallizer conditions, charcoal and graphite flakes are all important parameters that affect the performance of the copper rod. The casting rod speed needs to match the solidification process of the copper rod. When the casting rod speed is too fast, the height of the liquid cavity in the crystallizer increases, and defects such as cracks, pores and hollow rods are easily generated; when the casting rod speed is slow, it not only affects the output but also easily generates surface cracks. The crystallizer is the core of the upward continuous casting process. Its function is to use the siphon principle to suck the liquid oxygen-free copper into the crystallizer, and the copper rod uses heat exchange to quickly and evenly cool and crystallize the copper into copper casting rods. Charcoal mainly plays the role of covering, heat preservation and deoxidation. By isolating the air from direct contact with the copper liquid, it prevents the high-temperature copper liquid from absorbing oxygen and hydrogen from the air to achieve the purpose of deoxidation.

Claims

1. A method for producing ultra-high purity oxygen-free copper rod by upward continuous casting, characterized in that: The following steps are involved: S1: cathode copper sheet is selected as raw material; S2: Add the dried electrolytic copper sheet and charcoal into the melting furnace, adjust the melt temperature of the cathode copper in the melting furnace to 1150±5℃, and maintain the copper liquid level at 500mm~580mm; S3: The molten copper liquid flows to the transition bin for static removal of impurities. 80mm to 200mm thick baked charcoal and graphite flakes are laid on the surface of the copper liquid to further reduce and purify the copper liquid. The ash and slag generated in the furnace bin are cleaned in time, and new charcoal is added. During the process, ensure that the copper liquid cannot be exposed to the air; S4: insert the graphite crystallizer into the copper liquid, connect the guide rod and start preparing the guide rod, adjust the inlet water temperature of the crystallizer to 20℃~30℃, the outlet water temperature to 25℃~45℃, the inlet and outlet temperature difference to 5℃~15℃, the water pressure to 0.2MPa~0.3MPa, set the traction speed of the casting rod to 1m / min~1.5m / min, and the pitch to 3mm~4mm; S5: After the rod is led out, the guide rod is disassembled in sections and enters the take-up system through the guide wheel frame, the intermediate bracket and the limit device, and the produced copper rod is randomly inspected.

2. The method for producing ultra-high purity oxygen-free copper rod by upward continuous casting according to claim 1, characterized in that: In step S2, the liquid level of the copper liquid is maintained at 530 mm to 550 mm.

3. The method for producing ultra-high purity oxygen-free copper rod by upward continuous casting according to claim 1, characterized in that: In step S3, the thickness of the charcoal and graphite flakes laid on the surface of the copper liquid is 100 mm to 150 mm.

4. The method for producing ultra-high purity oxygen-free copper rod by upward continuous casting according to claim 1, characterized in that: In step S4, ensure that the graphite crystallizer is inserted into the copper liquid to a depth of 150 mm to 170 mm.

5. The method for producing ultra-high purity oxygen-free copper rod by upward continuous casting according to claim 1, characterized in that: In step S1, the surface of the selected cathode copper sheet is smooth and flat without obvious surface defects, and the content of impurity elements is controlled to be: As≤10ppm, Fe≤30ppm, Sb≤10ppm, Bi≤10ppm, Pb≤10ppm.

Citation Information

Cited By

  • Process for producing high-purity oxygen-free copper rod by up-drawing method

    CN120662773A

  • System and method for prolonging service life of side-blown molten pool smelting furnace

    CN122216994A